2016
DOI: 10.1158/0008-5472.can-16-0138
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Antimetastatic Effects—Letter

Abstract: We were surprised by the results of Choi and colleagues showing that urokinase exerts antimetastatic effects by dissociating clusters of circulating tumor cells (1).It is well known that the role of urokinase (uPA) in cancer is not limited to the vascular compartment, but is also a critical component of the tissue-invasive system used by cancer cells.It is true that, as previously described, polymerized fibrin is a determinant for tumor dissemination by supporting tumor cell migration, through stabilizing tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…However, preclinical data suggest that urokinase exerts antimetastatic effects by dissociating CTC-clusters [53]. In the light of these findings, our results grant further studies investigating the role of urokinase in CTC clustering and metastatic seeding ability, as urokinase treatment may also increase the risk of tumor cell invasiveness and metastatic spreading [54]. On the other hand, we observed an increased expression of CDK4 and E2F4 in tumor cells isolated from ZF-cluster, genes regulating cell cycle progression.…”
Section: Discussionsupporting
confidence: 69%
“…However, preclinical data suggest that urokinase exerts antimetastatic effects by dissociating CTC-clusters [53]. In the light of these findings, our results grant further studies investigating the role of urokinase in CTC clustering and metastatic seeding ability, as urokinase treatment may also increase the risk of tumor cell invasiveness and metastatic spreading [54]. On the other hand, we observed an increased expression of CDK4 and E2F4 in tumor cells isolated from ZF-cluster, genes regulating cell cycle progression.…”
Section: Discussionsupporting
confidence: 69%
“…Choi et al reported the development of such a strategy using urokinase, which they claimed reduced the incidence of metastasis in animal models by lysing fibrin to dissociate CTC clusters[46]. Some have expressed skepticism in the potential use of urokinase for this application however, since urokinase has significant off-target and potentially detrimental effects in many patients[58]. Furthermore, since there is little evidence that fibrin is a significant component of CTC cluster adhesion, the mechanism of action in these studies may not in fact be related to cluster dissociation[58].…”
Section: Towards Clinical Utilitymentioning
confidence: 99%
“…Some have expressed skepticism in the potential use of urokinase for this application however, since urokinase has significant off-target and potentially detrimental effects in many patients[58]. Furthermore, since there is little evidence that fibrin is a significant component of CTC cluster adhesion, the mechanism of action in these studies may not in fact be related to cluster dissociation[58]. These points highlight how important it is that antimetastatic strategies targeting CTC clusters be highly specific and have minimal off-target effects.…”
Section: Towards Clinical Utilitymentioning
confidence: 99%
“…Based on the proposed and experimentally demonstrated increased metastatic potential of CTC clusters (relative to single CTCs), it has been suggested that their dissociation into single cells might be a valid therapeutic strategy to decrease their aggressivity (Aceto et al, 2014; Hong, Fang, & Zhang, 2016). Studies that directly targeted cell–cell connections and adhesion within clusters by downregulating the expression of plakoglobin (a protein involved in desmosomes and adherens junctions), inhibiting heparanase or administering a thrombolytic agent (Aceto et al, 2014; Choi et al, 2015; Lu, Zeng, Gu, & Ma, 2015; Wei et al, 2018) showed promise, but concerns regarding the side effects of such treatments have been raised (Choi, Yoon, & Yun, 2016; Mirshahi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%